Impact of Conservation Tillage on Soil Organic Carbon and Physical Properties - Sharma, Peeyush; Abrol, Vikas; Sharma, K. R.; Sharma, Neetu; Phogat, V. K.; Vikas, Vishaw (International Journal of Bio-resource and Stress Management, 2023)
Soil conservation tillage (CT) systems are considered major component of sustainable agriculture involves reducing the tillage operations and plant remains at the soil surface in the ratio of at least 30%. In this review we summarized how conservation tillage affects soil compaction, aggregation, hydraulic conductivity, porosity, water storage and soil organic carbon. Water storage and movement of water are strongly influenced by soil structure. Contradictory results have been published on the effect of different tillage systems on soil physical and chemical properties. Several studies showed that conservation tillage leads to positive changes in the physical and chemical properties of a soil and provide the best opportunity for restoring and improving soil productivity however the magnitude of changes varies with the nature of the soil, tillage operations, soil water content and climate. Some studies stated a decrease in total porosity, water holding capacity, soil organic carbon and greater bulk density under no tillage system than the intensive tillage systems. On the other hand, in long term experiments, it has been well documented that soil can be managed to increase SOC and improve soil physical properties by adopting conservation tillage. Intensive tillage can deteriorate the soil quality, because it incorporates crop residue into the soil, disrupts soil aggregates, and increases soil aeration. However, short-term ( 20 yr).